Sport and Physical Activity in People With a Stoma and After Ostomy Surgery: A Narrative Review - Psiuk, Arkadiusz Adam (Quality in Sport, 2026)
Background: Ostomy surgery — colostomy, ileostomy, or urostomy — entails anatomical, metabolic, and psychosocial changes that may discourage participation in sport. Reduced physical activity appears common in this population, although the stoma itself is seldom a genuine contraindication to exercise. Aim: To synthesise current knowledge on the safety, benefits, barriers, and recommendations concerning sport and physical activity in patients after ostomy procedures. Material and methods: A narrative review was undertaken. Searches in PubMed, Scopus, Web of Science, and the Cochrane Library identified guidelines, reviews, and primary studies addressing physical activity, abdominal exercise, parastomal hernia, fluid and electrolyte balance, and psychosocial adaptation in people living with a stoma. Results: The available literature suggests that appropriately tailored activity may improve quality of life, fatigue, and physical fitness, whereas inactivity is widespread and often related to fear of parastomal hernia, altered body image, and depressive symptoms. Recurring themes include graded core-focused training, avoidance of uncontrolled rises in intra-abdominal pressure, hydration strategies for ileostomy, and protective measures for contact sports. The evidence base remains limited and heterogeneous, with few randomised trials. Conclusions: Sport appears generally feasible and potentially beneficial after ostomy surgery when individualised and supported by interdisciplinary care. Adequately powered trials are needed to define optimal training protocols.